The evolving (re)categorisations of refugees throughout the "refugee/migrant crisis". (24th February 2017) - Goodman, Simon; Sirriyeh, Ala; McMahon, Simon
Abstract: The UK media's reporting of events in 2015 contained constantly evolving categorisations of people attempting to reach Europe and the UK, each with different implications for their treatment. A discourse analysis of UK media outputs charts the development of the terminology used to present the crisis and those people involved. First, "Mediterranean migrant crisis" was used to present those involved as "migrants" to be prevented from reaching Europe. Next, it became a "Calais migrant crisis" in which migrants were constructed as a threat to UK security and then the "European migrant crisis" an ongoing threat to Europe. Photographs of a drowned child led to a shift to a "refugee crisis" in which refugees were presented in a humane and sympathetic way. When terrorist attacks were linked with the crisis, refugees reverted to migrants. Findings are discussed regarding the impact of categorisation on debates about the inclusion and exclusion of refugees.